Performance and carcass traits of broilers fed ‘wood ash digested maize cobs’ based diets fortified with grandizyme (2012)
The growth and carcass traits of broilers were investigated using 200 unsexed day old chicks. Wood ash digested maize cobs (WADMC) fortified with grandizyme at graded levels were incorporated in the diet and used to assess the performance and carcass traits of the experimental birds. In a completely randomized design, 40 birds were assigned to each of the five dietary treatments A-E. The control A had no WADMC and no enzyme, while diets B, C, D and E had 5, 10, 15 and 20% inclusion levels of WADMC respectively with 5g of the enzyme per 100kg of feed. Starter diets with these inclusions were fed to birds from day-old. Data collected include the feed intake, weight gain, organ and carcass weights. The results obtained revealed that the birds fed diets B, C and D digested the maize cobs based diets fortified with enzymes betterl as reflected in the primal cuts from carcass and were significantly different (P<0.05) than from treatments A and E. The feed intake of birds in treatment A and E significantly differed from that of treatments B, C and D Birds in treatment E recorded high incidence of prolapsed. It could be concluded that the performance and carcass characteristics of WADMC based diets at 10 and 15% levels of inclusion fortified with 5grams of enzyme was better those on 5 and 20%.